Human Obesity Induces Dysfunction and Early Senescence in Adipose Tissue-Derived Mesenchymal Stromal/Stem Cells - Conley, Sabena M.; Hickson, LaTonya J.; Kellogg, Todd A.; McKenzie, Travis; Heimbach, Julie K.; Taner, Timucin; Tang, Hui; Jordan, Kyra L.; Saadiq, Ishran M.; Woollard, John R.; Isik, Busra; Afarideh, Mohsen; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background: Chronic inflammatory conditions such as obesity may adversely impact the biological functions underlying the regenerative potential of mesenchymal stromal/stem cells (MSC). Obesity can impair MSC function by inducing cellular senescence, a growth-arrest program that transitions cells to a pro-inflammatory state. However, the effect of obesity on adipose tissue-derived MSC in human subjects remains unclear. We tested the hypothesis that obesity induces senescence and dysfunction in human MSC. Methods: MSC were harvested from abdominal subcutaneous fat collected from obese and age-matched non-obese subjects (n=40) during bariatric or kidney donation surgeries, respectively. MSC were characterized, their migration and proliferation assessed, and cellular senescence evaluated by gene expression of cell-cycle arrest and senescence-associated secretory phenotype markers. In vitro studies tested MSC effect on injured human umbilical vein endothelial cells (HUVEC). Results: Mean age was 59±8 years, 66% were females. Obese subjects had higher body mass index (BMI) than non-obese. MSC from obese subjects exhibited lower proliferative capacities than non-obese-MSC, suggesting decreased function, whereas their migration remained unchanged. Senescent cell burden and phenotype, manifested as p16, p53, IL-6, and MCP-1 gene expression, were significantly upregulated in obese subjects’ MSC. BMI correlated directly with expression of p16, p21, and IL-6. Furthermore, co-incubation with non-obese, but not with obese MSC, restored VEGF expression that was downregulated in HUVEC. Conclusion: Human obesity triggers an early senescence program and proliferative dysfunction in adipose tissue-derived MSC. Thus, obesity-induced cellular injury may alter efficacy of this endogenous repair system and hamper the feasibility of autologous transplantation in obese individuals.